Screening of Pure ILs and DESs for CO2 Separation, N2O Separation, and H2S Separation Processes. (18th February 2023) - Zhang, Yingying; Yang, Xuzhao; Han, Jingli; Tian, Junfeng; Zhang, Ting; Li, Yakun; Zhang, Jiangqiang; Shi, Yuxin; Zhang, Jingjing
Abstract : Ionic liquids (ILs) are proposed as potential "green" solvents with remarkable properties. Deep eutectic solvents (DESs) are a new type of ILs with additional properties, such as higher biodegradability and a lower price. ILs and DESs are "green" absorbents for various gas separations, such as CO2 /N2, CO2 /H2 /CO, H2 S/CH4, and N2 O/N2 . Due to their large number, the screening of ILs is crucial. Although ILs with high absorption capacities were screened using gas solubility and selectivity, it is important to consider the energy and solvents used in the process. In this paper, the absorbent amount and the energy consumption were used for screening absorbents for various gas separation processes. The results reveal that physical IL [Bmim][DCA] and chemical IL [Eeim][Ac] are screened for CO2 /N2 and CO2 /H2 /CO separation, physical IL [Omim][PF6 ] for H2 S/CH4 separation, and physical IL [P66614 ][eFAP] for NO/N2 separation. The screened ILs offer some advantages over commercial absorbents in terms of lower energy consumption or amount.